The heat-and-mass transfer during filtration drying of feedstock for slag gravel production. Research of change of temperature of thermal agent is on height of layer of material - Atamanyuk, V; Barna, I; Symak, D (Видавництво Львівської політехніки, 2014)
In the article the results of experimental and theoretical researches are presented heatand mass-transfer during the filtration drying of feedstock for slag gravel production. Timehistory of temperature of thermal agent is experimentally investigational on the height of layer of dry and moist raw material materials and dependence of speed of moving of mass-transfer zone is certain on a temperature.Подано результати експериментальних і теоретичних досліджень тепло- і масообміну під час фільтраційного сушіння сировинних матеріалів виробництва шлакового гравію. Експериментально досліджено зміну температури теплового агента в часі по висоті шару сухих та вологих сировинних матеріалів та визначено залежність швидкості переміщення зони масообміну від температури.
Keywords: filtration drying; heat agent.; slag; clay; raw granules; heat - and - mass transfer; фільтраційне сушіння; шлак; глина; сирцеві гранули; тепло- і масообмін; тепловий агент